Causes of Audit Report Lag with Reputation of Audit Firm as a Moderating Variable - Widiastuti, Afifah Nur; Rofiqoh, Ifah (Integrated Journal of Business and Economics (IJBE), 2024)
Audit report lag is an important problem because it can cause delays in submitting financial reports by companies to the OJK. This study examines the effect of audit opinion, profitability, and company size on audit report lag with Reputation of audit firm as a moderating variable in non-primary consumer goods companies listed on the IDX. The sample used in this study were 78 non-primary consumer goods companies listed on the IDX 2018-2022. The data analysis method used in this research is panel data regression analysis and moderation regression analysis. The results of this study indicate that audit opinion and profitability have a negative effect on audit report lag, while company size has no significant effect on audit report lag. Reputation of audit firm is able to strengthen the effect of profitability on audit report lag and weaken the effect of company size on audit report lag and but is unable to moderate the effect of audit opinion on audit report lag.